Digital games that fight misinformation in the context of a virtual exchange within Sub-Saharan Africa and the EU - Nicolaou, Anna; Nicolaidou, Iolie; Hadjiconstantinou, Stavroulla; Makindi, Stanley; Mushima, Muke; Oscar, Mwale (My University, 2025)
Fake news identification on social media is a complex, still unresolved issue for students. Digital games have been used to teach fake news identification in social media with promising results but have not been examined in the context of virtual exchanges. The study implements digital games that fight misinformation and fake news in the context of virtual exchanges and examines their effectiveness in students’ understanding of misinformation techniques. Participants included 158 secondary and higher education students from six countries (three European and three Sub-Saharan African countries) who participated in the first cycle of the virtual exchange curriculum that was designed as part of the DigiTREE project and were asked to play the Bad News game. Students’ knowledge of misinformation techniques significantly increased from M=76.31 (SD=16.97) before the game to M=80.91 (SD=18.04) after the game [t (102) =-3.56, p =0.001]. Results suggest that accessible mobile games effectively combat misinformation in virtual exchanges, even among countries with limited internet access. They also serve as effective short-term interventions, significantly increasing students’ awareness of misinformation techniques like impersonation, spreading conspiracy theories, discrediting opponents, and trolling. Future research can explore whether learning gains from students’ simulated interactions within the games transfer to real-world, more complex environments.